ANALISIS FRAMING BERITA DESAKAN STATUS BENCANA NASIONAL BANJIR SUMATERA DI KOMPAS.COM - Alifah Rose Wiana; Abdul Rasyid (Fakultas Ilmu Komunikasi Universitas Teknologi Sumbawa, 2026)
This study aims to analyze the media framing of Kompas.com regarding public demands for the establishment of a national disaster status following the floods and landslides in Sumatra at the end of 2025. The research employs a descriptive qualitative approach using the framing analysis model proposed by Robert N. Entman, which consists of four elements: problem definition, causal interpretation, moral evaluation, and treatment recommendation. The data consist of three news articles published by Kompas.com between November and December 2025, highlighting demands from political actors, religious leaders, and civil society organizations. The findings reveal that Kompas.com frames the disaster as a humanitarian crisis that exceeds the capacity of local governments, with causes attributed not only to natural factors but also to structural and policy failures. From a moral perspective, the media emphasizes the state's responsibility to protect its citizens while criticizing the slow response of the central government. The recommended solution consistently highlighted is the declaration of a national disaster status to accelerate resource mobilization, improve inter-agency coordination, and enable access to international aid. The study also identifies two dominant framing patterns, namely structural criticism and humanitarian framing, reflecting the media’s role as a social control mechanism and a bridge for public aspirations during crises. These findings underline that media not only disseminate information but also shape public perception and influence policy accountability Keywords: Media Framing, National Disaster, Kompas.com, Sumatra Flood, Entman Analysis